Phytochemicals May Arrest HIV-1 Progression - Sharma B. (Journal of Clinical Research In HIV AIDS And Prevention, 2014)
This hypothesis‑driven review considers phytochemicals with putative anti‑HIV activity. It summarizes proposed mechanisms, in vitro evidence, and formulation issues, and calls for standardized assays and clinical trials to determine real‑world efficacy and safety.